Flying to the moon: Impactful accounts of triatomines invasion from the 2nd to the 13th floor of an urban residential building in the municipality of Rio Branco, Acre, Brazil - Moura, Manoella da Silva; da Silva, Luciana Braga; Madeira, Fernanda Portela; Das Neves, Francisco Warcron Oliveira; Menezes, André Luiz Rodrigues; da Rosa, João Aristeu [UNESP]; de Oliveira, Jader; Camargo, Luís Marcelo Aranha; Ribeiro, Mariane Albuquerque Lima; Meneguetti, Dionatas Ulises de Oliveira (FapUNIFESP (SciELO), 2024)
Background: Vectorial transmission through hematophagous triatomine insects remains the primary mode of Chagas Disease contagion. These insects have become increasingly common in urban environments. Therefore, this study aimed to report an encounter of triatomines with trypanosomatid infection in a vertical residential condominium in Rio Branco, the capital of the state of Acre, in the western Brazilian Amazon. Methods: Triatomines were collected from residents and sent to the municipality's Entomological Surveillance sector. Trypanosomatid positivity was evaluated using optical microscopy, followed by species and genotype identification using molecular biology techniques. Results: Twenty-five adult triatomine specimens were collected from two of three condominium buildings invading apartments from the 2nd to 13th floors. Six specimens were identified as Rhodnius sp. and 19 as R. montenegrensis. Among these, molecular tests were conducted on seven specimens, with five testing positive for Trypanosoma cruzi, all belonging to genotype TcI. Conclusions: These findings underscore the need for further studies to better understand the invasive capacity of these insects in these environments and the mechanisms involved in this process.
Keywords: Amazon; Chagas disease; Vectors